Biochemical sensors : mimicking gustatory and olfactory senses - Toko, Kiyoshi, 1953- (Singapore : Pan Stanford Publishing, 2013)
This book is the first to comprehensively treat sensors for gustatory and olfactory senses. It will be highly useful to students and researchers in a wide variety of scientific fields and also to those in the fields of foods, perfumes, medicines and robotics as the sensor applications.
Includes bibliographical references and index.
Keywords: Biochemical engineering; Olfactory receptors; Olfactory sensors; Taste -- Molecular aspects; Chemical senses